How Are Emotional Intelligence Development Efforts in Improving Social Skill in Autistic Children? - Indi Rahmawati; Azam Syukur Rahmatullah (FKIP Universitas Lampung, 2024)
This research aims to find out how methods and strategies can be applied in developing the emotional intelligence of children with autism, as well as the impact on their ability to interact with the social environment. Through approaches involving games, art, and relaxation techniques, children are taught to recognize and manage their own emotions, as well as understand the emotions of others. The research is a field study where researchers conducted research at Bina Anggita Yogyakarta. The approach used is a case study. Which explores a particular phenomenon, event, or situation in a real context to analyze and understand the complexity of a problem. The results of the study show that the improvement of emotional intelligence not only helps autistic children in their social skills but also increases self-confidence and more effective communication. With the right development methods, autistic children can make significant progress in social interaction, which supports their integration in society. This research provides important insights for parents, educators, and professionals in designing intervention programs that are appropriate for children with autism. More effective to support the development of children with autism. Keywords: emotional intelligence development, social skills, autistic children.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202499